Alcohol Use and Moffitt's Maturity Gap Thesis for Adolescent Offending: An Evolutionary Perspective and Analysis - Meghan L. Royle; Eric J. Connolly (Evolutionary Psychology, 2024)
While a wealth of research has focused on testing several arguments from Moffitt's developmental taxonomy of antisocial behavior—mainly the presence of life-course-persistent vs. adolescence-limited offending and predictors of each trajectory—much less attention has been devoted to examining how evolutionarily adaptive lifestyle factors common during adolescence may condition the relationship between the maturity gap and delinquent offending. One factor that may play a role during this period of development is alcohol use, as many adolescents begin to experiment with consuming alcohol in varying degrees in social settings to model adult-like behaviors. Yet presently much is unknown about the role of alcohol use on the association between the maturity gap and delinquency. The current study aims to address this void in the literature by analyzing data from a U.S. sample of adolescent males ( N  = 1,276) to assess whether alcohol use moderates the relationship between the maturity gap and delinquent behavior. Findings suggest that the maturity gap is associated with delinquent behavior and that the association becomes weaker at higher levels of alcohol use. The implications of these findings for Moffitt's maturity gap thesis and male offending from an evolutionary perspective are discussed.